Використання барди у технології виробництва житньо-пшеничного хліба - Лобачова, Надія Леонідівна; Сабaдаш, Сергій Михайлович (НТУ "ХПІ", 2017)
У статті проаналізовано сучасний стан та перспективність переробки післяспиртової барди – вторинного продукту при виробництві біоетанола з кукурудзи, обґрунтовано і досліджено шляхи її використання в хлібопекарській промисловості. Наведено харчовий потенціал продукту. Для проведення науково-дослідних робіт із сушіння післяспиртової барди було розроблено технологічний процес та технологію житньо-пшеничного хліба на заквасках. Досліджено склад мікрофлори житніх заквасок та їх роль у формуванні якості хліба.

A secondary product of the production of bioethanol is pislyaspyrtova dry bard, which is a raw material that incorporates contains proteins, fats, carbohydrates, and essential amino acids. Hence the search for ways to use it as an alt ernative raw material in technology baking industry since bread - this is the daily hand food among the population. The article analyzes the current state and prospects of processing pislyaspyrtovoyi bards - a secondary product in the production of bioethanol from corn, reasonably and explored ways to use baking industry. An edible product potential. For the research work of drying pislyaspyrtovoyi bards was developed manufacturing process technology and rye - wheat bread yeast. Studied the composition of microflora of sourdough rye and their role in shaping the quality of bread. On this basis, the author PSBC reasonably possible use in a biologically valuable raw materials in the production of bakery industry. Based on research organoleptic, physical, chemical and microbiological parameters PSBC reasonable prospects of using technology in rye-wheat bread. Past studies prove the effectiveness of the use of technology PSBC preparation rye sourdough in the production of rye-wheat bread, produces high quality products that meet the requirements of regulatory documents. To conduct research projects on drying of PSBC was developed process technology and rye - wheat bread to leaven. The composition of the microflora of sourdough rye and their role in shaping the quality of bread.
Bards use in production technologies rye-wheat bread
Keywords: післяспиртова барда; кукурудза; біоетанол; білок; закваска; хліб; corn; bioethanol; white; sourdough bread